Quantifying the potential health risk of surface waters in the Qinling giant panda habitat - Zheng, Ying-Juan; Chen, Yi-Ping; Zhao, Yan; Maltby, Lorraine; Liu, Wan-Gang (Frontiers in Environmental Science, 2024)
The giant panda (Ailuropoda melanoleuca) is recognized worldwide as an icon for wildlife conservation. The Qinling subspecies (Ailuropoda melanoleuca qinlingensis) inhabiting the Qinling Mountains is more endangered. Previous studies have indicated that Qinling pandas are potentially at risk from environmental pollutants, which they are exposed to via food and drinking water. However, there is little information on the surface water quality in Qinling Mountain and it is unknown whether drinking water is an important pollutant source for pandas. Water samples were collected from five different nature reserves in Qingling, each of which is home to a population of pandas. Samples were analyzed for five essential metals of copper (Cu), zinc(Zn), manganese (Mn), chromium (Cr), nickel (Ni) and four non-essential metals of lead (Pb), cadmium (Cd), arsenic (As), mercury (Hg). Concentrations of all heavy metals (HMs) were higher in buffer zones than in the core areas and were highest in Foping and Niuweihe nature reserves. Concentrations of mercury exceeded the water quality standard in core zone of three reserves, suggesting that NWH (Niuweihe), THS (Tianhuashan) and PHL (Pingheliang) giant panda populations were at risk from mercury toxicity. The accumulation of other elements over time could also pose a serious risk to pandas. Three main sources of pollution were identified: coal combustion, waste incineration and fertilizer use; traffic-related activities and metal mining. Environmental pollution is compromising efforts to conserve the giant panda and measures need to be put in place to control pollution sources.